Skin permeation of nickel, cobalt and chromium salts in ex vivo human skin, visualized using mass spectrometry imaging. (October 2021) - Hagvall, Lina; Pour, Masoumeh Dowlatshahi; Feng, Jiabao; Karma, Moshtak; Hedberg, Yolanda; Malmberg, Per
Abstract: Skin permeation and distribution of three of the most common skin sensitizers was investigated using a previously developed animal-free exposure method combined with imaging mass spectrometry. Nickel, cobalt, and chromium (III) salts were dissolved in a buffer and exposed to human skin ex vivo, to be analyzed using time of flight secondary ion mass spectrometry (ToF-SIMS). Our findings demonstrate that metal haptens mainly accumulated in the stratum corneum, however all three metal sensitizers could also be detected in the epidermis. Cobalt and chromium (III) species penetrated into the epidermis to a larger extent than nickel species. The degree of penetration into the epidermis is suggested to be affected by the sensitization potency of the metal salts, as well as their speciation, i.e. the amount of the respective metal present in the solution as bioaccessible and solubilised ions. Our method provided permeation profiles in human skin for known sensitizers, on a level of detail that is not possible to achieve by other means. The findings show that the permeation profiles are different, despite these sensitizers being all metal ions and common causes of contact allergy. Studying skin uptake by only considering penetration through the skin might therefore not give accurate results. Highlights: Skin permeation/distribution of nickel, cobalt and chromium (III) was investigated. An animal-free exposure method combined with imaging mass spectrometry was used. The metals accumulated in stratum corneum but could also be detected in epidermis. Co and Cr(III) penetrated into the epidermis to a larger extent than Ni species.